Genetic polymorphism of cytochrome P450 2C19 in healthy Malaysian subjects - Yang, Y.S.; Wong, L.P.; Lee, T.C.; Mustafa, A.M.; Mohamed, Zahurin; Lang, C.C. (Blackwell Publishing, 2004)
Aims Impaired S-mephenytoin 4'-hydroxylation is a well-described genetic polymorphism affecting drug metabolism in humans. Although ethnic differences in its distribution of polymorphism has been described, it is not known whether there is an ethnic heterogeneity of the structure and expression of the CYP2C19 enzyme in the Malaysian population. Methods Study subjects were 142 healthy, unrelated Malaysians aged 18-29 years. Baseline omeprazole and 2-h postingestion omeprazole and 5'-hydroxyomeprazole concentrations were measured for CYP2C19 phenotype determination. Identification of CYP2C19 genotypes was performed with the use of polymerase chain reaction. Results Phenotyping of CYP2C19 revealed that the prevalence of poor metabolizers (PMs) in the Malaysian population was 14.1, whereas prevalence of PMs in genotyping was 12.6. The PM genotypic prevalence rate was 5.6 in Malays, 19.1 in Chinese and 10.0 in Indian subjects. There were significant differences in PM genotypic prevalence rates among the three primary ethnic groups (P less than or equal to 0.05). Conclusions Phenotyping and genotyping revealed significant differences in the prevalence rates among the three ethnic groups in Malaysia, with Chinese recording highest prevalence.